WORD FORMATION PROCESSES OF REGISTERS USED BY HAMSTER MALANG COMMUNITY IN FACEBOOK - DEWI, WAHYU HANGGAR (Jurnal Ilmiah Mahasiswa FIB, 2014)
Dewi, Wahyu Hanggar. 2014. Word Formation Processes of Register Used By Hamster Malang Community in Facebook.  Study Program of English, Department of Languages and Literature, Faculty of Cultural Studies, Universitas Brawijaya. Supervisor: Emy Sudarwati;Co-Supervisor: Ida Puji LestariKeywords: Sociolinguistics, Word Formation Processes, Register, Hamster Malang Community, facebook group “Jual Beli Hamster”Register is another complicating factor in any study of language varieties. Registers are sets of language items associated with discrete accupational or social group. In this case the writer is interested  in studying  the registers used by Hamster Malang Community in Facebook. There are three problems of the study, namely; (1) What are the  registers used by Hamster Malang Community? (2) What are the meaning of registers that used by Hamster Malang Community? and (3) What are the word formation processes of the registers used by Hamster Malang Community? This study is qualitative research which aims at getting the description about registers used by Hamster Malang Community. It was conducted not only to understand but also to describe the implementation of the registers used by Hamster Malang Community in Facebook.  This study used  the meaning  of register  to analyze the registers used by Hamster malang Community.  This study has found out 56  registers used by Hamster Malang Community. The register is classified into three, namely; register of borrowing consisting of 22 terms, register of acronym consisting 25  terms and register of clipping consisting 9 terms used by Hamster Malang Community in facebook. Register is a variety of language and its use in specific community and situation. Thus, the meanings and their usages are significant for communication.  It can be concluded that registers are very specific in meaning used in some community, especially in Hamster Malang Community. The writer hopes to the further researchers to do similar field on register with different techniques and subjects in  order to give more contribution to the study of linguistics. Actually with new complete references and also different object to study. The writer hopes that this study will be a great  method  to conduct deeper analysis on Sociolinguistics.